13 Correlation of interventricular systolic relationship and infarct size in acute myocardial infarction. (26th April 2015) - Garg, P; Kidambi, A; Ripley, DP; Dobson, LE; Swoboda, PP; Musa, TA; McDiarmid, AK; Erhayiem, B; Greenwood, JP; Plein, S
Abstract : Background: In an echocardiographic study investigating interventricular systolic relationship in healthy individuals, the absolute value of tricuspid annular plane systolic excursion (TAPSE) is greater than the mitral annular plane of systolic excursion (MAPSE) by 54.5% and the MAPSE/TAPSE ratio is 0.66 ± 0.14. However, the interventricular systolic relationship has not been accurately defined in the presence of regional wall motion abnormalities. We hypothesised that the interventricular systolic relationship, measured by the ratio of averaged-MAPSE and TAPSE, changes in the presence of acute myocardial infarction (AMI). Methods: Thirty-eight patients underwent CMR at 3T (Achieva CV, Philips Healthcare, Best, The Netherlands) within 3 days following AMI. Cine and LGE imaging (16–20 min following 0.1 mmol/kg gadolinium DTPA) were performed. Infarct location was determined by location of LGE in the infarcted area. MAPSE (medial, lateral and average) and TAPSE were measured from the 4-chamber cine (Figure 1 ). The infarct volume was measured from LGE images by Otsu method. Results: The MAPSE/TAPSE ratio in acute-MI patients was significantly reduced compared to reported normal values (0.56 ± 0.14 vs 0.66 ± 0.14; p = 0.003). LV ejection fraction (EF) correlated most closely with averaged MAPSE (r = 0.45; p = 0.004). The interventricular systolic relationship significantly correlated with left ventricular end-diastolic indexed volume (LVEDVi) (r = −0.46; p = 0.009) and infarct volume (r = −0.36; p = 0.04). Conclusion: The ratio of averaged-MAPSE/TAPSE is significantly reduced in patients with acute-MI and correlates with infarct size. In cases where acute-MI is suspected, this parameter of interventricular systolic relationship may provide a simple additional diagnostic tool for both echocardiography and CMR assessment. Funding: JPG and SP receive a research grant from Philips Healthcare. SP is funded by British Heart Foundation fellowship (FS/10/62/28409).